Calculus
posted by Steff .
Am I right so far?
G(x)=e^x sqrt(1+x^2)
=e^x(1+x^2)^1/2
=e^x(1/2)(1+x^2)^1/2(2x) + e^x(1+x^2)^1/2
So I used product rule, chain rule, and exponential function with base e

It's good so far.
You can simplify a little by cancelling the 2's in the numberator and denominator of the first term.
Respond to this Question
Similar Questions

Product Rule
Can someone please help me with this? f(x)=(x2)^1/2 * (x^23)^3 find f'(x) using the product rul. This is what I came up with I just need to know if I did it right. f'(x)=(x2)^1/2*3(x^23)+(x^23)^3*(1)^1/2 Hopefully I did. Thanks. 
Math  Calculus Question.
hey can someone explain to me the relationship between the chain rule and implicit differentiation? 
Math, Calculus
Find the derivative of the function. y= xcosx  sinx What's the derivative? 
Calculus
How do I use the chain rule to find the derivative of square root(1x^2) also, are there any general hints or tips for determining when the chain rule and product or quotient rule should be used? 
calculus
how do not understand how to find a deriviative of this function? 
Calc I
How do I find the derivative for the sqrt(sin(e^(x^3)*cos(x)))? 
calculus please help asap
true or false questions: a)The derivatives of the reciprocal trigonometric functions can be found using the chain rule and their related base functions. b) A sinusoidal function can be differentiated only if the independent variable … 
Calculus
Match the rule with the title: ____ 3. d/dx [f(x)/g(x) ]=(g(x) f^' (x)f(x) g^' (x))/[g(x)]^2 ____ 4. d/dx [f(g(x))]=f^' (g(x))∙g'(x) ____ 5. d/dx [f(x)∙g(x)]= f(x) g^' (x)+g(x) f^' (x) ____ 6.d/dx [x]=1 ____ 7. d/dx [f(x)+g(x)]= … 
Math (Calculus)
Hello, Could somebody please help me with the following question? 
Calculus
We just learned derivatives and now on the Chain Rule. y = r/[(sqrt)(r(sqrd)+1)] y' = [[(sqrt)(r(sqrd)+1)(r)']  [(r)(sqrt)(r(sqrd)+1)']] / [(sqrt)(r(sqrd)+1)](sqrd) y' = (sqrt)(r(sqrd)+1)  r[1/2(r(sqrd)+1)(raised to 1/2)](2r) My …